Geomorphological and stratigraphic analyses at the archaeological excavation in the Megapark, Nyíregyháza-Oros - Buró, Botond; Jakab, Attila; Lóki, József (Journal of Environmental Geography, 2011)
The aim of our morphological and stratigraphic investigations at the archaeological excavation in the area of the Megapark at Nyíregyháza–Oros is to make the reconstruction of the Aeolian development of the study area more accurate. The excavation is located between the rem-nants of two abandoned river beds in a wind-blown sand area near the crossing of main roads 4 and 41 East of Nyíregyháza–Oros. Eight bore-holes were drilled in the site of the excavation. The cores were sampled in order to perform the sedimentological analysis of the penetrated strata. Strata of the sand dune are divided by a fossil soil horizon in which a cemetery from the age of the Hungarian conquest was found. Underneath the cemetery findings from the imperial age and urn graves from the Bronze Age were excavated. This suggests that wind-blown sand covered the soil horizon in a thickness of 1-1.5 m by the age of the conquest. The 3-4 m thick wind-blown sand excavated from the findings indicates sand accumulation following the 10th century.